Lichens as a promising natural antibacterial agent against fish pathogens - (:unkn) unknown (EUR ASSOC FISH PATHOLOGISTS, 2019)
Lichens are symbiotic organisms composed of fungi and algae. They have been used as a treatment of various diseases through the ages. This study was carried out to investigate the potential antibacterial effects of 13 lichen species (Anaptychia ciliaris, Bryoria capillaris, Cetraria islandica, Evernia divaricata, Evernia prunastri, Letharia vulpina, Lobaria pulmonaria, Platismatia glauca, Pseudoevernia furfuracea, Ramalina farinacea, Ramalina fastigiata, Ramalina fraxinea, and Usnea florida) against six common fish bacterial pathogens (Aeromonas hydrophila, Aeromonas salmonicida, Enterococcus faecalis, Lactococcus garvieae, Streptococcus agalactiae, and Yersinia ruckeri). Acetone, methanol and water extracts of lichen species were evaluated by using disc diffusion method. The majority of the lichen species exhibited antibacterial activity against A. hydrophila, S. agalactiae, E. faecalis and L. garvieae by the inhibition zones between 7.0 +/- 0.0-28.5 +/- 0.5 (mm +/- SE). However, none of the lichens produced an inhibitory effect against A. salmonicida and Y. ruckeri. In general, acetone extractions were found to be more effective than methanol and water extractions. This is the first report related to the bioactivity of lichens that especially focuses on fish pathogens. The study suggested that lichens may be a possible source of natural antibacterial agents in the fishery and aquaculture industries.
Keywords: ANTIMICROBIAL ACTIVITY; AEROMONAS-HYDROPHILA; EXTRACTS; INFECTION; ACID; SALMON; PLANTS